Hermann Göring and the Nazi art collection : the looting of Europe's art treasures and their dispersal after World War II - Alford, Kenneth D. (McFarland, 2012)
"By the end of World War II, the Nazis had plundered roughly one-fifth of the entire art treasures of the world. This work explores the history and formation of the Nazi art collection and the methods used by Hermann Göring and his party to strip occupied Europe of a large part of its artistic heritage"--Provided by publisher